Tourism and Intercultural Communication: A Theoretical Study - Achdiar Redy Setiawan (Jurusan Ilmu Komunikasi UTM, 2023)
All aspects of social life are involved in communication, which is an important component in the formation and processes of culture. In a modern society characterized by globalization, cultural diversity and intercultural dialogue are highly discussed topics. One of the main topics in the study of intercultural communication is cultural differences. Having an understanding of other people's cultures is essential to recognize the nature of these differences and to relate to others through an attitude of understanding and tolerance, which is the basis for actual intercultural discussions, especially in the field of tourism. Communication is an act of human connection, but it is culture that drives it. In tourism, the quality of communication is related to the culture and means used. The experience of intercultural communication not only helps travelers to learn and appreciate other cultures, but also helps them understand their own culture better.